Improving the Long-Term Mechanical Properties of Thermoplastic Short Natural Fiber Compounds by Using Alternative Matrices - Renato Lemos Cosse; Tobias van der Most; Vincent S. D. Voet; Rudy Folkersma; Katja Loos (Biomimetics)
Wood plastic composites (WPCs) offer a means to reduce the carbon footprint by incorporating natural fibers to enhance the mechanical properties. However, there is limited information on the mechanical properties of these materials under hostile conditions. This study evaluated composites of polypropylene (PP), polystyrene (PS), and polylactic acid (PLA) processed via extrusion and injection molding. Tests were conducted on tensile and flexural strength and modulus, heat deflection temperature (HDT), and creep analysis under varying relative humidity conditions (10% and 90%) and water immersion, followed by freeze—thaw cycles. The addition of fibers generally improved the mechanical properties but increased water absorption. HDT and creep were dependent on the crystallinity of the composites. PLA and PS demonstrated a superior overall performance, except for their impact properties, where PP was slightly better than PLA.